Credit-by-Examination As Seen by Secondary School Teachers and Coordinators of Accountability in Florida - Tully, G. Emerson ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
This paper reports the replies given by secondary school teachers and supervisors on a survey asking for their views on (1) the comparative merits of the descriptive materials for the College-Level Examination Program (CLEP) and the Advanced Placement Program (APP), and (2) the manner by which the two testing programs are now made available to high school students. Twenty-three supervisors and 309 teachers throughout Florida completed the survey. Their responses are reported in terms of frequency counts and percentages of responses to alternative positions. Results are discussed in terms of evaluation of (1) CLEP descriptive brochures and APP study outlines, and (2) the views of respondents toward testing and awarding of credit. (DT)
ERIC Note: Paper presented at the Southern Regional Meeting of the College Entrance Examination Board (New Orleans, Louisiana, February 18-20, 1976); Not available in hard copy due to marginal legibility of original document.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Advanced Placement Programs; College Credits; Evaluation; Higher Education; Mathematics Education; Surveys; Tests; College Level Examination Program; Reports, Research